(untitled) (ART AND CULTURE BULLETIN, 2024)
This article states that the vocal movements of each singer are controlled by a complex of sense organs. Therefore, every singer not only hears the sound that he wants to make, but also feels it. Every singer has a “voice body map” that includes different sensations from different organs and parts of the vocal apparatus.